Role of Hum Test in Diagnosis of Hearing Loss - Dhakal, Ashish; Shrestha, Bikash Lal; Karmacharya, Sameer; Pradhan, Aakash (Birat Journal of Health Sciences, 2020)
Introduction: The Hum Test is used by some otolaryngologists as an alternative to the Weber Test to detect the presence and type of acute hearing change; however, its use has not yet been formally validated. Objective: To compare the diagnostic performance of Hum test with Weber test to detect hearing loss taking pure tone audiometry as the gold standard. Methodology: A prospective, cross-sectional study was conducted in the department of Otorhinolaryngology and Head and Neck surgery, Dhulikhel Hospital- Kathmandu University Hospital, from June 2018 to February 2019. Total of 257 patients were enrolled in the study and were subjected to 3 tests: Weber test, Hum test, and pure tone audiometry. Results: When examining patients with hearing loss, sensitivity of Hum test and weber test were 60.3% and 93.8 % respectively. In patients with CHL, sensitivity of Hum test was 55.7% while Weber test was 94.8%. In SNHL, it was 74.6% for Hum test and 90.5% for Weber test. Likewise, according to laterality of disease, sensitivity of Hum test was 58.6% for unilateral hearing loss and 65.2% for bilateral hearing loss. For Weber test it was 96.3% for unilateral and 86.4% for bilateral disease. Conclusion: Hum test is not as sensitive as Weber test in diagnosis of hearing loss both for conductive and sensorineural hearing loss.